Checking the moderating effect of perceived control on the relationship between anxiety and postoperative hospital length of stay among coronary artery bypass graft patients - AbuRuz ME; Al-Dweik G; Al-Akash HY (International Journal of General Medicine, 2019)
Mohannad Eid AbuRuz, Ghadeer Al-Dweik, Hekmat Yousef Al-Akash Clinical Nursing Department, Faculty of Nursing, Applied Science Private University, Amman 11934, Jordan Background: Coronary artery disease (CAD) is the most common cardiovascular disease (CVD). Coronary artery bypass graft (CABG) surgery is the most common treatment used for CAD. Patients undergoing this surgery are always anxious, which might increase complications in the postoperative period, especially prolongation of postoperative length of stay (LOS). It has been shown that perceived control (PC) moderated the relationship between anxiety and complications in a cardiac population, but its effect has not been studied in post-CABG. Aim: The aim of this study was to check if there is a moderating effect for the PC on the relationship between anxiety and LOS post-CABG. Patients and methods: A non-experimental, prospective, observational study was conducted with a consecutive sample of 250 patients who underwent elective CABG from four hospitals in Amman, Jordan. PC was measured by the Arabic version of the Control Attitude Scale-Revised (CAS-R), and anxiety was measured by the Arabic version of the anxiety subscale of Hospital Anxiety and Depression Scale. LOS and other needed information were obtained from patients’ medical records. Results: Preoperative anxiety was significantly higher than postoperative anxiety (mean [SD]: 12.80 [6.70] vs 11.01 [6.74], P<0.001). Female patients were more anxious and had longer LOS compared to male patients. In stepwise regression, anxiety and PC scores were independent predictors for LOS. Every unit increase in preoperative anxiety increased LOS by 0.381 days, and every unit increase in PC decreased the postoperative LOS by 0.210 days. Moderating effect was checked by simple slope analysis for high (+1 SD) and low (−1 SD) levels of PC. Patients with high anxiety and low PC had the longest LOS, and patients with low anxiety and high PC had the shortest LOS, indicating the moderating effect of PC on the relationship between anxiety and LOS. Conclusion: High levels of anxiety were associated with longer LOS after CABG. PC moderates this relationship. Enhancing PC in this population can improve outcomes and decrease LOS and morbidity. Keywords: anxiety, perceived control, length of stay, coronary artery bypass graft